Mosquito Bite‐Avoidance Attitudes and Behaviors in Travelers at Risk of Malaria. Issue 1 (9th July 2013) - Goodyer, Larry; Song, John
Abstract Introduction Mosquito bite prevention is an important strategy to reduce the risk of contracting malaria and advice on the methods available should be offered in pre‐travel consultations. This study examines the attitudes of a cohort of UK travelers to the various bite‐avoidance strategies and the extent to which they are practiced when visiting malaria‐endemic areas. Method This was a retrospective cohort study of UK travelers above 18 years of age returning from malaria‐endemic areas. Those who agreed to participate were emailed a Web‐based questionnaire on their return to the UK. The questionnaire consisted of items relating to attitudes to bite‐avoidance measures and malaria and the use of bite‐avoidance measures while away. Results One hundred and thirty‐two travelers completed the questionnaire representing a 51% response rate. Frequent use of repellents (69%) was higher than covering the arms (49%) and legs (56%), or using insecticide vaporizers (16%), sprays (24%), and bed nets (32%). Those under the age of 30 tended to use bite avoidance less frequently. Gender, purpose, and duration of travel were also found to influence the use of particular measures. A reliable 17‐point attitude to the bite‐avoidance questionnaire (Cronbach's alpha = 0.70) was constructed and a subscale score indicated that attitudes influenced the use of repellents. Conclusion The use of measures to avoid mosquito bites on retiring and covering arms and legs needs to be further emphasized to travelers. The attitude scales described could be a useful tool in practice and research into this area.